2022
DOI: 10.3389/fonc.2022.827777
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body MRI Is an Effective Imaging Modality for Hematological Malignancy Treatment Response Assessment: A Systematic Review and Meta-Analysis

Abstract: ObjectivesTo evaluate the diagnostic accuracy of whole-body MRI (WB-MRI) for assessment of hematological malignancies’ therapeutic response.MethodsPubMed, Embase, and Web of Science were searched up to August 2021 to identify studies reporting the diagnostic performance of WB-MRI for the assessment of hematological malignancies’ treatment response. A bivariate random-effects model was applied for the generation of the pooled diagnostic performance.ResultsFourteen studies with 457 patients with lymphoma, multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Studies have also found that PET-CT is less accurate than WB-MRI in the diagnosis of indolent NHL due to the lack of FDG avidity in those patients. Lin G et al conducted a systematic review in 457 patients with either lymphoma, multiple myeloma, or sarcoma, and compared PET-CT to WB-MRI with diffusion-weighted imaging and WB-MRI without DWI [ 33 ]. They found that WB-MRI with diffusion-weighted imaging had a sensitivity of 94% for the detection of the aforementioned diseases, which was statistically significantly higher than the 88% sensitivity of WB-MRI without DWI [ 33 ].…”
Section: Imaging Of Lymphoma In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also found that PET-CT is less accurate than WB-MRI in the diagnosis of indolent NHL due to the lack of FDG avidity in those patients. Lin G et al conducted a systematic review in 457 patients with either lymphoma, multiple myeloma, or sarcoma, and compared PET-CT to WB-MRI with diffusion-weighted imaging and WB-MRI without DWI [ 33 ]. They found that WB-MRI with diffusion-weighted imaging had a sensitivity of 94% for the detection of the aforementioned diseases, which was statistically significantly higher than the 88% sensitivity of WB-MRI without DWI [ 33 ].…”
Section: Imaging Of Lymphoma In Pregnancymentioning
confidence: 99%
“…Lin G et al conducted a systematic review in 457 patients with either lymphoma, multiple myeloma, or sarcoma, and compared PET-CT to WB-MRI with diffusion-weighted imaging and WB-MRI without DWI [33]. They found that WB-MRI with diffusion-weighted imaging had a sensitivity of 94% for the detection of the aforementioned diseases, which was statistically significantly higher than the 88% sensitivity of WB-MRI without DWI [33]. The primary conclusion of the study was that "WB-MRI All," which combined all sequences, had the highest sensitivity and specificity for the assessment of lymphoma when comparing to PET-CT, by 100% [34].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Malignant lesions usually have a smaller ADC value than benign lesions as a result of the narrow cytoplasm of tumor cells and the limited diffusion of water molecules [ 11 ]. At present, DWI has been applied for cancer diagnosis [ 12 ], tumor grading [ 13 ], and treatment response assessment [ 14 ]. Unfortunately, there is a large overlap in ADC values between different grades and types of tumors, making it unreliable to diagnose individual brain tumors using DWI alone [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%